1996
DOI: 10.1074/jbc.271.50.32411
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila α-Catenin and E-cadherin Bind to Distinct Regions of Drosophila Armadillo

Abstract: Adherens junctions are multiprotein complexes mediating cell-cell adhesion and communication. They are organized around a transmembrane cadherin, which binds a set of cytoplasmic proteins required for adhesion and to link the complex to the actin cytoskeleton. Three components of Drosophila adherens junctions, analogous to those in vertebrates, have been identified: Armadillo (homolog of ␤-catenin), Drosophila E-cadherin (DE-cadherin), and ␣-catenin. We carried out the first analysis of the interactions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 50 publications
(60 reference statements)
4
94
0
Order By: Relevance
“…In Drosophila, adherens junctions consist of the same components as in vertebrates: E-cadherin (DE-cadherin), ␤-catenin, which is encoded by the segment polarity gene armadillo (arm) and ␣-catenin (Cox et al, 1996;McCartney et al, 2001;Oda and Tsukita, 1999;Pai et al, 1996;Tepass et al, 1996;Uemura et al, 1996). Arm is also an essential component of the Wingless (Wg) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, adherens junctions consist of the same components as in vertebrates: E-cadherin (DE-cadherin), ␤-catenin, which is encoded by the segment polarity gene armadillo (arm) and ␣-catenin (Cox et al, 1996;McCartney et al, 2001;Oda and Tsukita, 1999;Pai et al, 1996;Tepass et al, 1996;Uemura et al, 1996). Arm is also an essential component of the Wingless (Wg) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that bcatenin associates with the cytoplasmic domain of Ecadherin via its internal armadillo repeats (Hulsken et al, 1994;Huber and Weis, 2001). In addition, the Nterminal armadillo repeats of b-catenin associate with a-catenin, which in turn binds directly with F-actin (Pai et al, 1996). E-cadherin, a-and b-catenin do not have any SH3 domains and the associations among them are thus, not SH3-mediated.…”
Section: Ucs15a Does Not Disrupt Non-sh3-mediated Protein ± Protein Imentioning
confidence: 99%
“…In addition, the reduced expression of PTEN protein as well as increased Akt activity has been observed in xenograft models (27). Recently, it has been shown that PTEN inhibits PI3K/Aktstimulated androgen-promoted cell growth and AR-mediated transcription in prostate cancer cells (28). PISK/Akt has been shown to promote prostate cancer cell survival and growth via enhancing AR-mediated transcription.…”
Section: Fig 7 B-catenin Augments Ar-mediated Transcription In Human mentioning
confidence: 99%
“…It has been shown that most ^-catenin-binding proteins such as Tcf/LEF family members (24), axin (25), APC (26,27), and cadherins (26,28) bind (3-catenin mainly through the central armadillo repeats. In most of cases, the first 10 repeats are required for the interactions, and a minimum of 6-7 repeats are sufficient for detectable binding (29,30).…”
Section: Armadillo Domain Of^-catenin Is Responsible For Binding To Amentioning
confidence: 99%